As políticas públicas educacionais para educação do campo: o caso de escolas em assentamentos de reforma agrária do município de Santana do Livramento/RS - Paprosqui, Juliane (2023)
Investigating how and if Educational Public Policies aimed at Rural Education are carried out in Municipal Elementary Schools, located within agrarian reform settlements in the city of Santana do Livramento, or that serve their populations, was the objective of this thesis that presents itself. The discussions and deliberations on the National Curriculum Guidelines for Rural Education were delimited from the first conference for Rural Education, which took place in 1998 in the city of Luziânia GO. This temporal space was necessary for the understanding of how these Guidelines have been practiced since then, in the Rural Schools surveyed. The method used in the study was based on the cycle of policies and qualitative analyzes based on the data evidenced by the various instruments used here. This made it possible to find out which public agents were involved, what roles were played by each one given the specific curricular guidelines, and if these are practiced in the school day to day, also understanding the difficulties in practicing them and what is the responsibility of each one in this educational scenario. It was also possible to verify external factors to the performance of public policies, such as rural development models in these places, strongly marked by the concentration of land in the past, as well as disputes and investments by capital in the territory of Rural Education today, tensions these who continue to fuel the struggles for the right to a quality basic education in and in the countryside.